Effect of Nitrogenous Fertilizer on Grain Yield and Grain Protein Concentration in Winter Wheat - SONMEZ, FAHRI (Asian Journal of Chemistry, 2010)
Baking quality of wheat in commercial cultivars generally depends on the protein concentration of the grain. Grain yield and grain protein concentration (GPC) in wheat is influenced by genotype and nitrogeneous fertilizer. However, nitrogeneous fertilizer can increase residual soil nitrate after harvest. The purpose of this study was to evaluate the effect of nitrogeneous fertilizer on grain yield, GPC and the relation grain yield and GPC in winter wheat. The experiments were conducted during two growing seasons in Tokat conditions of Turkey. Four nitrogen treatments (50, 100, 150 and 200 kg N/ha) were applied on two cultivars (Bezostaja-I and Momtchill). GPC and grain yield varied depending mainly on the year, genotype and nitrogen rates. Nitrogeneous fertilizer increased grain yield and GPC. However, the increases in grain yields were not significant when increasing from 100 kg N/ha to higher nitrogen rates. GPC was significantly affected by nitrogen rate (except for Momtchill in 2002) and GPC increased along with increasing nitrogeneous fertilizer rates, but the responses to added nitrogen were variable in genotypes and years. GPC in Bezostaja-I increased in a quadric manner as grain yield increased, whereas in Momtchill, the response was linear (in 2002). The results of this study show that high rates of nitrogeneous fertilizer may increase GPC and grain yield. On the other hand, the application of nitrogen at rates (more than 100-150 kg N/ha) exceeding plant utilization represents an unnecessary input cost to wheat producers and may contribute to the leaching of soil nitrate into the ground water. Therefore, the requirements for high GPC and grain yield must be accompanied by farm practices that make efficient use of the nitrogeneous fertilizer and minimize the risk of nitrate losses to water supplies.